Decomposing the trade-environment nexus for Malaysia: what do the technique, scale, composition, and comparative advantage effect indicate? - Ling, C.H.; Ahmed, K.; Muhamad, R.; Shahbaz, M. (2015)
This paper investigates the impact of trade openness on CO2 emissions using time series data over the period of 1970QI-2011QIV for Malaysia. We disintegrate the trade effect into scale, technique, composition, and comparative advantage effects to check the environmental consequence of trade at four different transition points. To achieve the purpose, we have employed augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) unit root tests in order to examine the stationary properties of the variables. Later, the long-run association among the variables is examined by applying autoregressive distributed lag (ARDL) bounds testing approach to cointegration. Our results confirm the presence of cointegration. Further, we find that scale effect has positive and technique effect has negative impact on CO2 emissions after threshold income level and form inverted U-shaped relationship-hence validates the environmental Kuznets curve hypothesis. Energy consumption adds in CO2 emissions. Trade openness and composite effect improve environmental quality by lowering CO2 emissions. The comparative advantage effect increases CO2 emissions and impairs environmental quality. The results provide the innovative approach to see the impact of trade openness in four sub-dimensions of trade liberalization. Hence, this study attributes more comprehensive policy tool for trade economists to better design environmentally sustainable trade rules and agreements.